STUDY OF FACTORS INFLUENCED ON THE MARKET OF HOTEL SERVICES IN MODERN CONDITIONS - Labazevych, I. V.; Kosar, N. S. (The actual problems of regional economy development, 2024)
The war in Ukraine has presented unique challenges for various sectors of the economy, including tourism and the hotel business. The purpose of this study was to investigate the trends in the development of the hotel services market in Ukraine, its impact from the war, and the seasonality of demand in contemporary conditions. To achieve this goal, secondary marketing information was collected and analyzed, consumer survey results were conducted and analyzed, and observation methods were utilized. The results of the study allowed for a deeper understanding of the theoretical and methodological foundations regarding the application of synchro-marketing concepts in hotel operations, indicating the scientific novelty of the work. The research revealed that the supply in Ukraine's hotel services market decreased during the war, with many establishments closed due to safety concerns, lack of demand, technical issues, or damage from shelling. Negative factors influencing demand for hotel services in Ukraine included a decrease in the population of Ukraine, the number of foreigners visiting, and initially, the cessation of domestic tourism, not considering displaced persons. From the beginning of the full-scale invasion until today, there has been a redistribution of Ukraine's hotel services market geographically. However, despite the full-scale war, hotels continue to remain attractive to investors. In addition to the war, seasonality continues to impact the researched hotel market. It remains a crucial factor in the hotel industry, affecting demand, pricing policies, and overall business effectiveness. Accordingly, hotels employ various marketing strategies to adapt to seasonal fluctuations and maximize revenue. One key strategy is pricing strategy. To compare the impact of seasonality on the hotel market in Lviv and Zakarpattia regions, a comparison of hotel prices in these regions during different periods of the year was conducted. The research showed that prices for accommodation in hotels unevenly increase during holidays, particularly in areas associated with ecotourism development. Considering seasonal demand, hotels can utilize other marketing tools besides seasonal discounts and offers, such as developing tailored offers for different target customer groups. The collected and analyzed primary marketing information demonstrates that even today, amidst war conditions, there are significant prospects for further development of Ukraine's hotel sector. It is critically important for hotel owners to select their locations wisely, formulate pricing policies, and continue to focus on these parameters in organizing their marketing communications to enhance their competitive positions. This underscores the practical value of the conducted research.